The influence of different forms of early childcare on children's emotional and behavioural development at school entry. Issue 5 (29th August 2012) - Stein, A.; Malmberg, L.‐E.; Leach, P.; Barnes, J.; Sylva, K.; ,
Abstract Background Over the past few decades there has been a dramatic increase in maternal employment and, as a result, an increase in the use of non‐maternal childcare in the early years. The purpose of this longitudinal study was to examine, in a large representative English sample, the influence of different forms of childcare on children's behavioural and emotional development around the age of school entry. Methods A sample of 991 families, originally recruited when the children were 3 months old, was assessed around school entry age at 51 months. The main outcome variable was the children's emotional and behavioural functioning, measured by questionnaire completed by both mothers and teachers. A range of repeated assessments were carried out at different time points, including direct observation of the quality of maternal caregiving and observations of the quality of non‐parental care, and amount of time spent in different forms of care. Results The strongest and most consistent influences on behaviour and emotional problems were derived from the home, including lower socio‐demographic status, poorer maternal caregiving, parental stress/maternal mental health problems, as well as child gender (being a boy). Non‐parental childcare had small effects on child outcome. One finding that did emerge was that children who spent more time in group care, mainly nursery care, were more likely to have behavioural problems, particularly hyperactivity. Conclusions These findings suggest that interventions to enhance children's emotional and behavioural development might best focus on supporting families and augmenting the quality of care in the home.